The Potential of Probiotics from Fermented Rice Water on Fibroblast Proliferation and Migration: A Systematic Review - Nury Nur Melati Tanjung; Dian Widiyanti; Indra Kusuma; Dicky Budiman (Indonesian Journal of Global Health Research, 2026)
Fermented rice water (FRW) has been traditionally used for skin care, but its biological mechanisms on fibroblasts, key cells in wound healing, have not been fully characterized. This systematic review aims to evaluate the efficacy of FRW on fibroblast proliferation and migration and to identify the molecular pathways involved. A literature search was conducted through PubMed, Scopus, and Google Scholar using the keywords "fermented rice water," "fibroblast," and "wound healing" in publications from 2015 to 2025. Studies were included if they evaluated the effects of FRW on fibroblasts in vitro or in vivo. Risk of bias was assessed using SYRCLE RoB (Risk Of Bias). Four studies met the inclusion criteria. FRW increased fibroblast viability by up to 116% and accelerated diabetic wound closure from 27% to 71% compared to controls. Molecular analysis showed upregulation of Collagen I mRNA by 17%, Collagen III by 47%, and Elastin by 159%. FRW activated the NRF2 pathway, which increased the expression of antioxidant enzymes (SOD, CAT, HO-1) and decreased inflammatory mediators including TNF-α, NF-κB, and MMP-1. Bioactive metabolites from Lactobacillus plantarum, Bacillus cereus, and Aspergillus oryzae played a role in these therapeutic effects. FRW shows potential as a fibroblast bio-stimulator through multi-pathway modulation involving extracellular matrix synthesis, antioxidant, and anti-inflammatory effects, with prospects for application in chronic wounds and anti-aging that require further clinical validation.